2013
DOI: 10.4995/wrs.2013.1148
|View full text |Cite
|
Sign up to set email alerts
|

NIRS of body and tissues in growing rabbits fed diets with different fat sources and supplemented with Curcuma longa

Abstract: A portable Near Infrared Reflectance Spectroscopy (NIRS) instrument was applied to 40 growing rabbits to determine body and tissue differences induced by experimental factors. The rabbits were examined at 2 live sites, in 7 warm carcass tissues and in longissimus dorsi muscle samples prepared in ethanol. For this purpose, the method was applied in a bi-factorial experiment concerning the dietary oil source (O) (maize vs. palm oil) and Curcuma longa (C) supplementation (0 and 3 g/kg, respectively). Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some years ago, Peiretti et al [21] concluded a study on NIRS of body and tissues in growing rabbits fed diets with different fat sources and supplemented with Curcuma longa with the phrase "New portable NIRS devices could be profitably used to test discriminant dietary effects on rabbit meat". Availability of a totally new instrument, the NIR-SCÏO smart, cheap and complete, enabled us to reach the far shore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some years ago, Peiretti et al [21] concluded a study on NIRS of body and tissues in growing rabbits fed diets with different fat sources and supplemented with Curcuma longa with the phrase "New portable NIRS devices could be profitably used to test discriminant dietary effects on rabbit meat". Availability of a totally new instrument, the NIR-SCÏO smart, cheap and complete, enabled us to reach the far shore.…”
Section: Discussionmentioning
confidence: 99%
“…NIRS has been classically used in rabbit research to predict the nutritional parameters of feedstuffs [10,11] and the composition of hind-leg meat [12,13], to determine the intramuscular fat content in rabbit selection programs [14], and the composition of the fatty acids (FA) related to an organic production system [15]. A discriminating approach has been adopted in the experimental use of NIRS to ascertain technological or nutritional factors [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NIRS has demonstrated the potential to detect biophysical traits from animal excrement, saliva, and tissue samples that may be useful for a number of applications in wildlife management and conservation [31]. These include disease and parasite status [32,33], sex [10,34], species [35], age class [10,36], reproductive status [10,[37][38][39], stress levels [40,41], body composition [42,43], and nutritional state [44]. The development of portable field sensors and lower-cost NIRS instruments, particularly in comparison with the equipment required for conventional assays, is increasing interest in a wide range of ecological applications [31,45,46].…”
Section: Introductionmentioning
confidence: 99%